Knowledge and attitudes of tuberculosis management in San Juan de Lurigancho district of Lima, Peru - Elizabeth M. Kiefer; Theresa Shao; Olveen Carrasquillo; Pamela Nabeta; Carlos Seas (Journal of Infection in Developing Countries)
Background: Expansion of the health care workforce in Peru to combat tuberculosis (TB) includes both professional health care providers (HCPs) such as doctors and nurses, and non-professional HCPs such as community health workers (CHWs). We describe the knowledge and attitudes of these HCPs, and identify modifiable barriers to appropriate anti-tuberculosis treatment.